Knowledge Concerning Obesity as A Risk Factor for Blindness: Association with Body Mass Index - Nuraini, Nuraini; Hadi , Kuncoro; Fitriana, Rizni; Hafish R. Paratama; Aatifah N. F. Nisa; Amalia A. Fadilah; Rifda H. Az. Zahra (Jurnal EduHealth, 2023)
The prevalence of obesity is increasing worldwide. Obesity is associated with several eye diseases. This study assess whether knowledge regarding obesity as a risk factor for blindness is associated with the Body Mass Index (BMI). This is a correlative descriptive, cross-sectional study, in one of Branch Area of community organization “X”, Pondok Kelapa, East Jakarta. With a questionnaire, we assessed knowledge regarding obesity and the risk of blinding eye diseases. Subjects completed the questionnaire, and then height (m), weight (kg), waist circumference (cm) were measured and BMI values were calculated. Of the 44 subjects, 54.5% were women, 36.4% aged 51-60 years, 45% had high school education, and 31.8% were housewives. Based on BMI and waist circumference, 27% of subjects were overweight, 45% were obese, and 86% were with central obesity. There were 14 subjects (31.8%) with poor knowledge, 22 (50%) with sufficient knowledge, and 8 (18.2%) with good knowledge. The results of correlation analysis (Pearson Correlation) showed a significant relationship between knowledge and BMI (r=0.457, p = 0.002). As a conclusion, knowledge that obesity as a risk factor for blindness is associated with BMI (p = 0.002)